Has the accumulation of foreign reserves protect the Thai economy from financial crisis?: An approach of Empirical likelihood - Yamaka W. (2017)
© Serials Publications Pvt. Ltd. In this article, we analyzed the effect of the accumulation of foreign reserves to economic growth in Thailand. In order to estimate of this impact, we employed a kink regression model which has an ability to capture a structure changed in the relationship between foreign reserves accumulation and economic growth as well as identify the kink point of their relationship. However, we concern that the assumption of normality may yield biased estimation for model parameters of interest and its difficulty to specify the correct error distribution of the model. Hence, the maximum likelihood estimation might not be accurate. In this paper, we investigate the use of Empirical likelihood approach as a solution to this problem. To examine the performance of this estimatin, we conduct a simulation and experiment studues. Then, the approach is applied to analyze the effect of the accumulation of foreign reserves to economic growth in Thailand.